Gastric toxicity of Alendronate and Methotrexate in Walker 256 carcinosarcoma jaw model - Alves, Ana Paula Negreiros Nunes; Lima Verde, Maria Elisa Quezado; Silva, Paulo Goberlânio de Barros; Sousa, Fabrício Bitu; Mota, Mário Rogério Lima; Pessoa, Cláudia do Ó; Lotufo, Letícia Veras Costa; Moraes-Filho, Manoel Odorico de (Journal of Health & Biological Sciences, 2019)
Introduction: experimental animal models represent a key tool used to elucidate the mechanisms of action and toxicity of anticancer drugs. Objective: the purpose was to establish a correlation of neoplastic growth with the combinatorial therapeutic application of sodium alendronate (ALD) and methotrexate (MTX), and to evaluate the gastrointestinal toxicity of these drugs, in the rat Walker 256 carcinosarcoma inoculation model. Methods: female rats were selected and randomly distributed into 5 groups (n=10): negative control (NC), positive control (PC), MTX-treated group, ALD-treated group, and MTX-ALD-treated group (MTX/ALD). Tumor cells were inoculated as a suspension of 1x106cells/mL into the alveolar cavities produced by exodontia procedures. The following parameters were evaluated: body weight, tumor volume and percentage of tumor inhibition, and gastrointestinal toxicity. Results: the body weight variation was statistically significant between NC animals and PC animals, and between NC animals and ALD-treated group (p<0.01). Tumor volume variation was statistically significant between PC animals, MTX-treated group and MTX/ALD-co-treated group (p<0.05). Analysis of gastric toxicity of MTX-treated group reveled slight reduction of chief (Ch) and parietal (Pr) cellular populations; ALD-treated group exhibited gastric mucosa without histological alterations of Ch cells but intense reduction of Pr cellular population; and MTX/ALD-co-treated group presented reduction of Ch and Pr cellular populations. Conclusions: ALD does not elicit significant antitumor effects on Walker 256 carcinosarcoma cells and decreases antitumor effects of MTX due to toxicity on the gastric epithelium, which is intensified with MTX association.